Simulation and Implementation of Quasi-Z-Source Based Single-stage Buck/boost Inverter Fed Induction Motor - P. Shunmugakani; D. Kirubakaran (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Renewable power systems as distributed generation units often experience big changes in the inverter input voltage due to fluctuations of energy resources. Z-source inverter (ZSI) is known as a single-stage buck/boost inverter. The ZSI achieves voltage buck/boost in single stage, without additional switches. Triggering on state enables energy to be stored in inductors, which is released when at non-shoot-through state, followed by the voltage boost feature. The voltage-fed Z-source inverter/quasi-Z-source inverter (QZSI) has been presented suitable for photovoltaic (PV) applications mainly because of its single-stage buck and boost capability and the improved reliability.